Effectiveness of Financial Management in Schools at Educational Institutions - Simamora, Benjamin (Attractive : Innovative Education Journal, 2022)
School is an educational institution in which the teaching and learning process is carried out and contains elements that are interconnected, these elements consist of educational technician staff consisting of school principals and teachers, administrative staff, school committees whose job is to help implement it. effectiveness of education, and students as learners. This study uses the library research method by applying a qualitative approach. And also this research uses literature data sources from books and journals related to the effectiveness of school financial management in Islamic education institutions. Data collection is done by tracing related references digitally. Then the collected data is displayed and constructed into a new concept. The results of this study include matters related to school financial management, the purpose of financial management in implementing school financial management is to meet funding needs related to school activities which can be carried out by planning in advance, trying to procure it, record it transparently and also use it to finance school programs effectively and efficiently, utilization of school finances, school financial resources consisting of the government, community funds, alumni funds and other sources and operational financing standards for educational units. Keywords: Effectiveness Financial Management, School Financial Management, Financial Management